Role of adenosine triphosphate and protein kinase A in the force-frequency relationship in isolated rat cardiomyocytes - Ozturk Nihal; Erkan Orhan; Uslu Serkan; Ozdemir Semir (Archives of Biological Sciences, 2023)
The physiological heart rate of rodents is around 4-6 Hz, although a stimulus frequency of 1 Hz is generally used in isolated cardiomyocytes to study changes in the contraction-relaxation cycle in cardiac muscle physiology and pathophysiology. Our study investigated the contraction parameters in isolated cardiomyocytes at 1, 2 and 4 Hz stimulation, and the roles of ATP and protein kinase A (PKA) in the force-frequency relationship in isolated cardiomyocytes. The contraction of the cell and intracellular Ca2+ changes were recorded simultaneously during cell stimulation by applying pulses of 6-8 V amplitude with frequencies of 1, 2 and 4 Hz. The increase in stimulus frequency caused a significant decrease in the percentage of shortening, relaxation times, slowing of the relaxation rate, and a significant increase in diastolic Ca2+ levels, but had no effect on the contraction rate and Ca2+ transients. Administration of ATP and N6-benzoyladenosine-3'-5'-cyclic monophosphate (6-BNZ-cAMP) caused an increase in contraction amplitude and speed which were proportional to the stimulus frequency but had no effect on the relaxation times. The experimental results show that the force-stimulus frequency has a negative correlation in isolated myocytes and that energy metabolism and the β-adrenergic system may be responsible for this relationship.